2015
DOI: 10.1002/2015gl064861
|View full text |Cite
|
Sign up to set email alerts
|

The influence of coral reefs and climate change on wave‐driven flooding of tropical coastlines

Abstract: A numerical model, XBeach, calibrated and validated on field data collected at Roi‐Namur Island on Kwajalein Atoll in the Republic of Marshall Islands, was used to examine the effects of different coral reef characteristics on potential coastal hazards caused by wave‐driven flooding and how these effects may be altered by projected climate change. The results presented herein suggest that coasts fronted by relatively narrow reefs with steep fore reef slopes (~1:10 and steeper) and deeper, smoother reef flats a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
292
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(337 citation statements)
references
References 37 publications
21
292
0
1
Order By: Relevance
“…Instead, locally generated wind waves played a critical role in determining the morphological change, with the wind waves reaching the shoreline ultimately being larger than the residual offshore waves that were transmitted across the reef. Although future climate changes are likely to increase wave transmission over coral reefs, primarily due to sea level rise but also due to degradation of reef habitats (Grady et al 2013;Quataert et al 2015), the results presented here show that while these structures still exist, they can provide natural coastal protection from offshore waves, even under extreme conditions. However, our results also reveal that even over the small scales (order 1 km) of a nearshore reef-lagoon system, local wind wave generation can play a dominant role in sediment transport and erosion responses during TC conditions, a process traditionally neglected in nearshore model applications to predict beach response to extreme events (e.g., models that can only consider remotely generated waves, such as Xbeach).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Instead, locally generated wind waves played a critical role in determining the morphological change, with the wind waves reaching the shoreline ultimately being larger than the residual offshore waves that were transmitted across the reef. Although future climate changes are likely to increase wave transmission over coral reefs, primarily due to sea level rise but also due to degradation of reef habitats (Grady et al 2013;Quataert et al 2015), the results presented here show that while these structures still exist, they can provide natural coastal protection from offshore waves, even under extreme conditions. However, our results also reveal that even over the small scales (order 1 km) of a nearshore reef-lagoon system, local wind wave generation can play a dominant role in sediment transport and erosion responses during TC conditions, a process traditionally neglected in nearshore model applications to predict beach response to extreme events (e.g., models that can only consider remotely generated waves, such as Xbeach).…”
Section: Resultsmentioning
confidence: 92%
“…Rigorously assessing the coastal protection afforded by reefs is particularly important given that a number of recent studies have suggested that the coastal protection offered by reefs is under threat due to both coral degradation (i.e., declining rates of net reef accretion and decreasing bottom roughness) and sea level rise, which will increase submergence depths and therefore expose reef-protected coastlines to larger waves (Grady et al 2013;Quataert et al 2015). Collectively, these studies emphasize that it is critical to understand the physical drivers of morphologic change in reef environments to better predict future changes to these coastlines.…”
mentioning
confidence: 99%
“…The oceanographic forcing that lead to this event has been documented in detail by Quataert et al [27] and Cheriton et al [48]. The large wave event, which had almost 7-m high waves with 15-s periods, coincided with a spring high tide and caused ocean water surface elevations, combined with wave run-up, to be 3.7 m above the reef flat, resulting in minor seawater flooding of select low-lying inland areas (Figure 7).…”
Section: Large Wave and Overwash Effectmentioning
confidence: 99%
“…Furthermore, the projected sea-level rise will outstrip potential new reef flat accretion, for optimal vertical coral reef flat accretion rates for coral reefs exposed to open-ocean storm waves are up to an order of magnitude smaller (1-4 mm/year per [22,23] than the rates of sea-level rise projected for the years 2000-2100 (8-16 mm/year per [24,25]). For Roi-Namur, this projected scenario results in a net increase in water depth over exposed coral reef flats at the order of 0.4-1.5 m during the 21st century, which will result in larger wave heights [26] and an increase of up to 200% in wave run-up [27], and may ultimately lead to a complete drowning of the islets [28].…”
Section: Study Areamentioning
confidence: 99%
“…Celui-ci constitue (i) le principal facteur naturel de déstabilisation de ces territoires [Larrue et Chiron, 2010 ;Laurent et Varney, 2014] (ii) un important facteur de risque futur, car le changement climatique engendre une augmentation de l'intensité des cyclones les plus intenses et une hausse (en voie d'accélération) de l'élévation du niveau de la mer. Cela devrait engendrer une hausse de la hauteur significative des vagues cycloniques, et du même coup, de leurs impacts destructeurs [Church et al, 2013 ;Hemer et al, 2013 ;Quataert et al, 2015]. Cet article présente la méthodologie adoptée et ses bénéfices pour la connaissance scientifique et pour les politiques publiques de réduction des risques liés à la mer et d'adaptation au changement climatique, en s'attachant à souligner : (1) l'intérêt de connaître la variabilité des impacts des événements météo-marins pour renforcer la résilience des territoires ; (2) le rôle du processus d'apprentissage issu des retours d'expérience post-événement dans la réduction de la vulnérabilité des territoires à ces événements ; (3) les facteurs qui jouent le rôle de « barrière » dans la réduction des risques et l'adaptation au changement climatique ; (4) les processus complexes et intrinsèquement liés, physiques et humains, qui soutiennent la résilience des atolls, et qui requièrent la mise en oeuvre de politiques d'adaptation spécifiques dans les territoires d'outre-mer français ; (5) le fait que les processus qui soutiennent la résilience d'un territoire, s'ils réduisent par certains leviers sa vulnérabilité, tendent aussi à faire émerger de nouvelles formes de vulnérabilité que les politiques publiques doivent anticiper et prendre en compte pour maximiser les bénéfices du processus d'apprentissage post-catastrophe [Duvat et al, 2016].…”
Section: Introductionunclassified